Does corporate social responsibility lead to superior performance? - Shu-Bing Liu; Hsin-Hong Kang; Shun-Jen Hsueh (Financial Studies, 2018)
In view of the inconsistent empirical findings in the literature and the limitations of least squares regressions, this paper employs a quantile regression method to investigate the impact that engagement in corporate social responsibility (CSR) activities has on corporate performance in China. An important finding of this work is that a significant, negative relationship across all quantiles exists between engagement in CSR activities and corporate performance in China when using return on assets (ROA), return on equity (ROE), and earnings per share (EPS) as performance measures. However, a significant, negative relationship between engagement in CSR activities and corporate performance only exists at low quantiles when using gross profit to net sales (GP) as a performance measure.
Keywords: C50; G30; 330; Corporate Performance; Quantile Regression